First finding of a dual-meaning X wave for phloem and xylem fluid ingestion: Characterization of Scaphoideus titanus (Hemiptera: Cicadellidae) EPG waveforms. (October 2017) - Chuche, Julien; Backus, Elaine A.; Thiéry, Denis; Sauvion, Nicolas
Graphical abstract: Highlights: Feeding waveforms were characterized and their biological meanings defined. Four typical waveform phases and four families within those phases were characterized. Sustained ingestion by a deltocephaline leafhopper can occur from both xylem and phloem vascular cells. EPG-recorded X wave was very similar to the model X wave of sharpshooters. Abstract: The leafhopper Scaphoideus titanus (Hemiptera: Cicadomorpha: Cicadellidae), an invasive deltocephaline species introduced into Europe from North America, is the vector of the most important phytoplasma disease in European viticulture, flavescence dorée. In this first electropenetrography (EPG) study of S. titanus, we characterized its feeding waveforms and defined their biological meanings. Four typical waveform phases (pathway, X wave, sustained ingestion, and interruption) and four families within those phases (A, B, C, and N) were characterized using DC EPG technology. We proposed biological meanings for these waveforms based on excreta pH-ingestion correlations, presence of X waves, and comparison with previous AC, DC, and AC-DC EPG waveforms conducted on Cicadomorpha. We observed that sustained (i.e., >10 min) ingestion by a deltocephaline leafhopper can occur from both xylem and phloem vascular cells. Waveform C2x represented ingestion of xylem fluid, and two waveforms represented behaviors when stylets were inserted into phloem sieve elements: C2p variant 1 (C2p-1), which may represent salivation (perhaps simultaneous with ingestion), and C2p variant 2 (C2p-2), which represented active ingestion. Furthermore, we found that the EPG-recorded X wave has a dual meaning by occurring prior to sustained ingestion from either phloem or xylem. This X wave was very similar in appearance to the model X wave of sharpshooters, an entirely different leafhopper subfamily, Cicadellinae. All cicadellines are obligate xylem-ingesters. Such a "dual-meaning X wave" will provide insights into how the feeding tactics of S. titanus relate to other sheath-feeding hemipterans, and will provide support for future research to clarify the role of this leafhopper as a vector of plant pathogens.